Palpa, Peru: Neue Forschungen zur Paracas-Kultur (800–200 v. Chr.) im Hochland Süd-Perus - Reindel, Markus (e-Forschungsberichte des DAI, 2023)
During the Formative period, the foundations for the first complex societies were laid in the Central Andes. The Paracas culture (800–200 BC) was the regional expression of the late Formative Period in southern Peru. While most research about the Paracas culture had focussed on grave offerings, especially ceramic and textiles, in this project we investigate the settlement patterns and socioeconomic structures of the Paracas culture. Our research in the highlands of the Palpa region has shown that the territory of the Paracas culture was much larger than previously thought and that sophisticated economic exchange systems had been established in order to take advantage of the diverse economy of a multitude of ecological regions in southern Peru.